1965
DOI: 10.1109/proc.1965.3814
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and quantum noise

Abstract: Thermal and Quantum Noise Abstracf-One purpose of &is article is to develop the theory of black body-radiation, thermal noise, and quantum noise from a few basic physical principles. A second purpose is to show how these resalts apply to certain areas such as antenna theory and ideal receivers. It is hoped that having this related material collected and presented in the language of the electronics engineer will be of tutorial value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(47 citation statements)
references
References 9 publications
0
46
0
1
Order By: Relevance
“…Straightforward, statistical proofs exist showing that if photon arrival rates are time-independent (i.e., they can be described as being a statistically stationary process), the total number of photons arriving during any time interval τ is Poissondistributed. 4 Theoretical studies have established the correspondence between the number of photons incident on the detector and the number of photoelectrons emitted, and thus the photoelectrons also have a Poisson distribution. 5 The probability of emitting n p photoelectrons during time τ is given by…”
Section: A Shot Noisementioning
confidence: 99%
See 1 more Smart Citation
“…Straightforward, statistical proofs exist showing that if photon arrival rates are time-independent (i.e., they can be described as being a statistically stationary process), the total number of photons arriving during any time interval τ is Poissondistributed. 4 Theoretical studies have established the correspondence between the number of photons incident on the detector and the number of photoelectrons emitted, and thus the photoelectrons also have a Poisson distribution. 5 The probability of emitting n p photoelectrons during time τ is given by…”
Section: A Shot Noisementioning
confidence: 99%
“…The derivation of the NSF is based on the fact that when the intensity of an incident light field does not fluctuate during the time of observation (i.e., when it remains in a statistically stationary state), photons sampled during this time will follow a Poisson stochastic process. 4,5 In Section 2 of the paper we review the statistical basis of photodetection. The mathematical derivation of the NSF is presented in Section 3.…”
Section: Introductionmentioning
confidence: 99%
“…For further reading on the general subject of thermal and quantum noise, see, for example, Oliver (1965) and Kerr et al (1997). Nityananda (1994) compares quantum issues in the radio and optical domains, and a discussion of basic concepts is given by Radhakrishnan (1999).…”
Section: Quantum Effectmentioning
confidence: 99%
“…This preserves the uncertainty relation at the expense of an added minimum noise power of hν at the input. Oliver (1965) has elaborated and generalized this argument to include all wavelength regimes, and has shown that the minimum total noise power spectral density ψ ν of an ideal amplifier (relative to the input) is…”
Section: Quantum Limits Of Amplifiersmentioning
confidence: 99%